Buds of Santonian magmatism associated with Marion hotspot in southern India. (9th December 2018) - Shaji, E.; Santosh, M.; Li, Shan‐Shan; Manikyamba, C.; Tsunogae, T.; Dhanil Dev, S.G.; Panicker, Arathi G.; Dhanakumar Singh, Th.; Subramanyam, K.S.V.
Abstract : Imprints of Marion hotspot magmatism representing the final stages of rifting between India and Madagascar from the Gondwana assembly occur scattered in several localities of southern India. In this study, we report evidence for rift‐related Santonian magmatism from alkali gabbro in the Madurai Block and present mineralogical, petrological, zircon U–Pb geochronological, and whole‐rock geochemical data on the Mundanmudi gabbroic complex. The rock shows mesocumulate textures with plagioclase laths forming the triple junctions and porphyritic texture with hornblende and clinopyroxene as phenocrysts. Geochemically, the gabbros are characterized by moderate to high SiO2 (50–58 wt.%), alkalies (4.14–7.00 wt.%), and high TiO2 (1.71–4.22 wt.%), with calc‐alkaline to high‐K alkaline affinity. Chondrite‐normalized REE patterns are highly fractionated with LREE enrichment relative to HREE and absence of Eu anomalies. The primitive mantle normalized trace element patterns have LILE enrichment relative to HFSE, exhibiting negative anomalies at Nb, Zr, and Ti. The HFSE relationships indicate a within‐plate tectonic setting for the genesis of these gabbros. The major element tectonic discrimination plots suggest MORB‐OFB affinity which is also supported by the Nb–Th relationship endorsing the divergent tectonic processes responsible for the generation of these gabbros. The zircon U–Pb mean age of ca. 85 Ma represents the magmatic emplacement age within a rift‐related tectonic setting during the Santonian (late Cretaceous). Based on the LREE and HREE relationship, it is inferred that the parental magma might have been derived at garnet lherzolite depths above the Marion plume, possibly correlatable with the large igneous province generated at this time in Madagascar. Our study provides new evidence for the final phase of the magmatism at ca. 85 Ma related to India–Madagascar rifting.